STUDI KEANEKARAGAMAN JENIS VEGETASI DI AREAL CALON KEBUN BENIH (KB) IUPHHK-HA PT. KAWEDAR WOOD INDUSTRY KABUPATEN KAPUAS HULU Studies of Vegetation Species Biodiversity in Sheed Orchards Candidate ( SO ) Area IUPHHK-HA PT. Kawedar Wood Industry - Kurniasari, Mareta; Budhi, Setia; Fernando, Togar (Universitas Tanjungpura, 2015)
Species diversity is a characteristic of a society based on levels of biological organization, can be used to express the structure of society. This study aims to determine the level of species diversity of vegetation and to determine the types of stands that have the potential as a producer of seed. The method used is a double plot method by means of laying in a systematic sample plot sampling. The dokument is taken from tree species, diameter and height were found on the growth rate at the level of the pole and tree level in 49 plots of observation. From the results obtained by the type of vegetation found in the area of seed orchards candidate showed a fairly high level of diversity, with the kind of stands that have the potential as a producer of seeds isVatica rassak, Shorea Leavis, Shorea parvifolia, Shorea sp, Shorea leprosula, Shorea ovalis, Dryobalanops beccarii and Dipterocarpus caudatus. Keywords : Diversity, vegetation and sheed orchards